2021
DOI: 10.1111/opn.12432
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of care homes workers’ views and training needs in relation to the use of socially assistive humanoid robots in their workplace

Abstract: Aim:The study aimed to explore the views and attitudes of care home workers about the socially assistive robot that was trialled in their workplace, in order to identify training needs in relation to the hypothetical future use of these robots in their workplace.Background: Care home workers face challenging workload conditions which may require the exploration of new solutions such as the use of socially assistive robots (SARs).Methods: This is a qualitative descriptive study which used semi-structured interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…This study found that the large majority of the participants ranked the item "[Robots] have no benefits" as 10 (least important), indicating an overwhelming degree of full acceptance of the benefits of SARs in health and social care, which is consistent with previous research (e.g., Papadopoulos et al, 2021;Yu et al, 2022 andZuschnegg et al, 2021). This was found across all the countries in the sample, and is all the more striking considering that only 10% of the participants had actually worked with or seen SARs in use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study found that the large majority of the participants ranked the item "[Robots] have no benefits" as 10 (least important), indicating an overwhelming degree of full acceptance of the benefits of SARs in health and social care, which is consistent with previous research (e.g., Papadopoulos et al, 2021;Yu et al, 2022 andZuschnegg et al, 2021). This was found across all the countries in the sample, and is all the more striking considering that only 10% of the participants had actually worked with or seen SARs in use.…”
Section: Discussionsupporting
confidence: 90%
“…This is an interesting contrast to the historical example and the findings of Broadbent et al (2012) discussed earlier. Most objections related to fears for patient safety should the SAR malfunction, closely followed by misgivings concerning depersonalized and dehumanized care, which closely resemble the themes identified in the study by Papadopoulos et al (2021) and Zuschnegg et al, 2021 discussed earlier. These latter objections relate to a key aspect of humanity and compassion.…”
Section: Discussionsupporting
confidence: 68%
“…However, concerns relating to the use of care robots, initial anxiety or fear, 27 or privacy issues, exist. 28 In contrast, our participants had a positive attitude toward care robots. This may be because our participants prioritized the importance of non-contact care due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 59%
“…The third domain relates to concerns that robots will replace human caregiving ( 17 ), especially with a rapid global ageing population and the insufficiency of available caregivers in long-term care settings ( 29 ). In such settings, care professionals have expressed similar fears that the use of robots could render their jobs obsolete and dehumanise care for people with dementia ( 30 ), however, such arguments relate more to socially assistive robots rather than pet robots.…”
Section: Introductionmentioning
confidence: 99%